2014
DOI: 10.1002/star.201400059
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, glycemic indices, and some factors affecting glycemic indices of underutilized tubers

Abstract: The present study was conducted to determine the proximate composition, glycemic indices (GIs), and some physicochemical properties of starch of boiled tubers of Dioscorea alata (violet and white), Maranta arundinacea, and Canna indica with the intention of recommending these for consumption or utilization as an ingredient in food preparation. Proximate compositions of cooked tubers were determined according to standard methods. GIs were determined according to FAO/WHO guidelines with bread as the standard. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…In total, the meta-analysis involved fifty-seven articles, as exhibited in Figure 1 . According to the Cochrane Collaboration tool, eleven trials [ 6 , 24 , 29 , 32 , 33 , 37 , 38 , 42 , 48 , 51 , 54 ] were categorized as being at a low risk of bias, while forty-four were categorized as unclear [ 17 , 19 , 20 , 21 , 22 , 23 , 25 , 27 , 28 , 30 , 31 , 34 , 35 , 36 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 52 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and two were categorized as being at a high risk of bias [ 18 , 26 ]. Details about the risk of bias are supplied in Figure 2 and Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, the meta-analysis involved fifty-seven articles, as exhibited in Figure 1 . According to the Cochrane Collaboration tool, eleven trials [ 6 , 24 , 29 , 32 , 33 , 37 , 38 , 42 , 48 , 51 , 54 ] were categorized as being at a low risk of bias, while forty-four were categorized as unclear [ 17 , 19 , 20 , 21 , 22 , 23 , 25 , 27 , 28 , 30 , 31 , 34 , 35 , 36 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 52 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and two were categorized as being at a high risk of bias [ 18 , 26 ]. Details about the risk of bias are supplied in Figure 2 and Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-seven studies, involving 936 participants, were published from 2002 to 2019. Twenty-six studies [ 9 , 10 , 11 , 12 , 17 , 18 , 20 , 21 , 26 , 31 , 35 , 39 , 43 , 44 , 45 , 46 , 47 , 49 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 ] used an in vitro experiment, while thirty-two studies involved in vivo experiments. Only one study used both in vitro and in vivo data experiments [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the proximate analysis of plainly boiled arrowroot rhizome, based on the findings of Senavirathna et al (2014), the former has lower fat (1.8%) and carbohydrate (64.0%) contents, but has higher protein (8.6%), ash (4.0%) and fiber (17.0%) contents than to seko and panganan, which can be attributed from varietal source and product ingredients used. Based on the results of this study, it has been found out that the best puto seko and panganan can be made by using 100% arrowroot starch, which was rated "like extremely" to "like very much" by the panelist.…”
Section: Proximate Analysismentioning
confidence: 97%
“…Senavirathna et al, (2014) reported that its boiled rhizome had 73.4% moisture, 1.8% fat, 8.6% protein, 4.0% ash, 64.0% carbohydrates, 11.0% insoluble dietary fiber and 6.0% soluble dietary fiber. Kumalasari et al (2012) reported that its starch has 11.9% moisture, 0.58% ash, 0.14% protein, 0.84% fat, 8.7% insoluble dietary fiber and 5.0% soluble dietary fiber, while Aprianita et al (2014) found it to have 10.2% moisture, 0.60% protein, 21.9% amylose and 62.3% amylopectin.…”
Section: Introductionmentioning
confidence: 99%